Karyotyping and prenatal diagnosis of 47,XX,+ 8[67]/46,XX [13] Mosaicism: case report and literature review - Shaohua Sun; Fang Zhan; Jiusheng Jiang; Xuerui Zhang; Lei Yan; Weiyi Cai; Hailiang Liu; Donghua Cao (BMC, 2019)
Abstract Background Trisomy 8 mosaicism has a wide phenotypic variability, ranging from mild dysmorphic features to severe malformations. This report concluded a female pregnant woman with trisomy 8 mosaicism, and carefully cytogenetic diagnoses were performed to give her prenatal diagnostic information. This report also provides more knowledge about trisomy 8 mosaicism and the prenatal diagnostic for clinicians. Case presentation In this present study, we reported one case of pregnancy woman with trisomy 8 mosaicism. Noninvasive prenatal testing prompted an abnormal Z-score, but further three dimension color ultrasound result suggested a single live fetus with no abnormality. The phenotypic of the pregnant woman was normal. Based on our results, there were no abnormal initial myeloid cells (< 10− 4), which suggested that the patient had no blood diseases. The peripheral blood karyotype of the patient was 47,XX,+ 8[67]/46,XX [13], and karyotype of amniotic fluid was 46, XX. The next generation sequencing (NGS) result suggested that the proportions of trisomy 8 in different tissues were obviously different; and 0% in amniotic fluid. Last, the chromosomes of the patient and her baby were confirmed using chromosome microarray analysis (CMA), and the results were arr[GRCh37](8) × 3,11p15.5p13(230750-33,455,733) × 2 hmz and normal. Conclusions This pregnancy woman was trisomy 8 mosaicism, but the phenotypic was normal, and also the fetus was normal. Carefully cytogenetic diagnoses should be performed for prenatal diagnose.